rms–Flux Slope in MAXI J1820+070: A Measure of Disk–Corona Coupling - Yanan Wang; Shuang-Nan Zhang (The Astrophysical Journal, 2024)
The linear rms–flux relation has been well established in different spectral states of all accreting systems. In this work, we study the evolution of the frequency-dependent rms–flux relation of MAXI J1820+070 during the initial decaying phase of its 2018 outburst with Insight-HXMT over a broad energy range of 1–150 keV. As the flux decreases, we first observe a linear rms–flux relation at frequencies from 2 mHz to 10 Hz, while such a relation breaks at varying times for different energies, leading to a substantial reduction in the slope. Moreover, we find that the low-frequency variability exhibits the highest sensitivity to the break, which occurs prior to the hard-to-hard state transition time determined through time-averaged spectroscopy, and the time deviation increases with energy. The overall evolution of the rms–flux slope and intercept suggests the presence of a two-component Comptonization system. One component is radially extended, explaining the strong disk–corona coupling before the break, while the other component extends vertically, contributing to a reduction of disk–corona coupling after the break. A further vertical expansion of the latter component is required to accommodate the dynamic evolution observed in the rms–flux slope. In conclusion, we suggest that the rms–flux slope in the 1–150 keV band can be employed as an indicator of disk–corona coupling, and the hard-to-hard state transition in MAXI J1820+070 could be partially driven by changes in the coronal geometry.